Land Conflicts in Sudan and Mechanisms of Conflict Resolution (A case Study of the Southern White Nile State) - Abdelatti, Hillo (Dirasat: Human and Social Sciences, 2021)
Land conflict worldwide has become an issue of concern for the researchers, politicians and planners. In this context, this paper investigates the land conflicts in the southern White Nile State, Sudan. The main objectives of the study are to explore the causes of conflicts, its impacts, and the mechanisms of conflict resolution. To achieve the objectives, the paper adopted the political economy approach, which combines both political and economic concerns in the analysis of land conflicts. The paper is mainly based on primary data collected during the fieldwork, using interviews and group discussions with various groups and decision makers. Moreover, the study is based on secondary data from both published and unpublished sources. The paper revealed that, the study area has experienced various kinds of land conflicts, notably between farmers and pastoralists, and between pastoralists themselves. The paper indicated that, land conflict constitutes one of the most serious challenges facing the area due to its negative impacts (i.e. loss of resources, land degradation, lack of social peace, and weakness of social relationships). The paper has come out with that, the irrational land policies adopted by government is the main factor behind the current conflicts in the area. The paper concluded that, conflict over land should be viewed from a different and broad perspective, therefore a comprehensive rural development and the elimination of structural and institutional obstacles are the only grantee for sustainable development and peaceful co-existence.